Comparative genomics and physiology of the butyrate‐producing bacterium Intestinimonas butyriciproducens. Issue 6 (9th November 2016) - Bui, Thi Phuong Nam; Shetty, Sudarshan Anand; Lagkouvardos, Ilias; Ritari, Jarmo; Chamlagain, Bhawani; Douillard, François P.; Paulin, Lars; Piironen, Vieno; Clavel, Thomas; Plugge, Caroline M.; de Vos, Willem M.
Summary: Intestinimonas is a newly described bacterial genus with representative strains present in the intestinal tract of human and other animals. Despite unique metabolic features including the production of butyrate from both sugars and amino acids, there is to date no data on their diversity, ecology, and physiology. Using a comprehensive phylogenetic approach, Intestinimomas was found to include at least three species that colonize primarily the human and mouse intestine. We focused on the most common and cultivable species of the genus, Intestinimonas butyriciproducens, and performed detailed genomic and physiological comparison of strains SRB521 T and AF211, isolated from the mouse and human gut respectively. The complete 3.3‐Mb genomic sequences of both strains were highly similar with 98.8% average nucleotide identity, testifying to their assignment to one single species. However, thorough analysis revealed significant genomic rearrangements, variations in phage‐derived sequences, and the presence of new CRISPR sequences in both strains. Moreover, strain AF211 appeared to be more efficient than strain SRB521 T in the conversion of the sugars arabinose and galactose. In conclusion, this study provides genomic and physiological insight into Intestinimonas butyriciproducens, a prevalent butyrate‐producing species, differentiating strains that originate from the mouse and human gut.